2006
DOI: 10.2106/jbjs.e.00674
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Joint Kinematics in Individuals with and without Patellofemoral Pain Syndrome

Abstract: It cannot be determined from our cross-sectional study whether the more lateral position of the patella in the group with clinical evidence of malalignment preceded or followed the onset of symptoms. It is clear from the data that an individual with patellofemoral pain syndrome cannot be distinguished from a control subject by examining patterns of spin, tilt, or lateral translation of the patella, even when clinical evidence of mechanical abnormality was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
76
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 23 publications
10
76
3
3
Order By: Relevance
“…The current study did find that PFPS patients had greater patellar and greater superior patellar translation from extension to flexion compared to controls, however, the remaining patellofemoral kinematics and contact area measurements between PFPS and healthy controls were not significantly different which corresponds with prior research in patellofemoral pain [17]. MacIntyre et al selected PFPS patients based on history and physical exam and found no differences in patellar spin (rotation), tilt, and lateral translation between PFPS and healthy controls across knee flexion ranges −4 to 60°, except for more lateral patellar translation at 19° of flexion in the PFPS group [17]. This is in contrast to the study that identified more lateral patellar displacement and patellar tilt in PFPS patients compared to healthy controls that defined patellar maltracking in adolescent patients with known history of patellar dislocation [23].…”
Section: Discussionsupporting
confidence: 84%
“…The current study did find that PFPS patients had greater patellar and greater superior patellar translation from extension to flexion compared to controls, however, the remaining patellofemoral kinematics and contact area measurements between PFPS and healthy controls were not significantly different which corresponds with prior research in patellofemoral pain [17]. MacIntyre et al selected PFPS patients based on history and physical exam and found no differences in patellar spin (rotation), tilt, and lateral translation between PFPS and healthy controls across knee flexion ranges −4 to 60°, except for more lateral patellar translation at 19° of flexion in the PFPS group [17]. This is in contrast to the study that identified more lateral patellar displacement and patellar tilt in PFPS patients compared to healthy controls that defined patellar maltracking in adolescent patients with known history of patellar dislocation [23].…”
Section: Discussionsupporting
confidence: 84%
“…high-intensity training). The combination of overload with dynamic valgus and functional lateralization of the patella may lead to overuse of the structures of the patellofemoral joint [43]. This overload may cause anterior knee pain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to adults, for whom PFP is often assumed to be a kinematic problem, overuse is most often cited as the etiology of pain for adolescent patients. 28, 44, 46, 47, 52 There are a plethora of analyses 6, 9, 12, 24, 37, 50 on patellar tracking and alignment patterns in adults with PFP. Yet, an extensive search of the literature revealed no studies on patellar tracking and just two studies 17, 33 on patellar alignment in adolescents with PFP.…”
Section: Introductionmentioning
confidence: 99%